2020
DOI: 10.1371/journal.pone.0228785
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-maternity deliveries in France: A nationwide population-based study

Abstract: Introduction In France, many maternity hospitals have been closed as a result of hospital restructuring in an effort to reduce costs through economies of scale. These closures have naturally increased the distance between home and the closest maternity ward for women throughout the country. However, studies have shown a positive correlation between this increase in distance and the incidence of unplanned out-of-maternity deliveries (OMD). This study was conducted to estimate the frequency of OMD in France, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
3
9
1
1
Order By: Relevance
“…The same French nationwide populationbased-study reported that the RR (95% CI) was 1.5 (1.4-1.5) for 16-30 km, 2.6 (2.4-2.9) for 31-45 km, and 3.9 (3.2-4.8) for 46-90 km with a reference of 0-15 km distance from the closest maternity unit. 5 However, contrary to those reports, the present results revealed that there was no significant increase in the rate of out-of-facility delivery in municipalities that were more than 30 km away from delivery facilities. In our study, the total number of deliveries was lower in municipalities that were farther away from delivery facilities, which may have made it difficult to find statistically significant differences.…”
Section: Relationship Between the Distance From The Nearest Delivery ...contrasting
confidence: 99%
See 3 more Smart Citations
“…The same French nationwide populationbased-study reported that the RR (95% CI) was 1.5 (1.4-1.5) for 16-30 km, 2.6 (2.4-2.9) for 31-45 km, and 3.9 (3.2-4.8) for 46-90 km with a reference of 0-15 km distance from the closest maternity unit. 5 However, contrary to those reports, the present results revealed that there was no significant increase in the rate of out-of-facility delivery in municipalities that were more than 30 km away from delivery facilities. In our study, the total number of deliveries was lower in municipalities that were farther away from delivery facilities, which may have made it difficult to find statistically significant differences.…”
Section: Relationship Between the Distance From The Nearest Delivery ...contrasting
confidence: 99%
“…Several national population‐based studies similar to this one have been conducted abroad. It was similar to the unplanned out‐of‐facility delivery rate of 1.4‰ for Finland with 1 052 559 deliveries 23 and 3.0‰ for France with 1 999 453 deliveries 5 . Delivery facilities are becoming centralized in Finland and France, with 9.9% and 25.3%, 5,24 respectively, living in locations more than 30 and 35 km away from the delivery facility.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Combier et al (2020) carried out a nationwide population-based study on unplanned out-of-maternity deliveries (OMD) in France. They found that women who delivered out-of-maternity had a higher risk of delivering before 37 weeks of gestation and that the risk of out-of-maternity delivery decreased for patients living in urban centres and in their surrounding suburbs [ 48 ]. In conclusion to their study, Pasternak et al (2018) noted that women with no caesarean deliveries and operative deliveries in their obstetric history are at greatest risk of unplanned out-of-hospital birth [ 32 ].…”
Section: Discussionmentioning
confidence: 99%